Qualidade de Vida Relacionada à Saúde de Pacientes com Insuficiência Cardíaca - ALMEIDA NETO, Omar Pereira de (2015)
Heart failure (HF) is a clinical challenge in the health area, having its progression epidemiological view, negatively impacting life quality related health ( HRQoL), presence of clinical signs related symptoms and disease gives treatments effects. This study aimed to evaluate general and specific HRQoL of patients with HF and characterize the clinical and socioeconomic profile or ourselves. Aimed to associate even with the HRQOL scores of clinical and socioeconomic predictors correlate to specific HRQOL to clinical and socioeconomic predictors with IC and generally correlate with HRQoL specific IC. Try cross up, quantitative and analytical study one, conducted with patients seen us Hospital Outpatient Cardiology Clinics of Uberlandia and Uberaba. The instruments used were: Clinical and socioeconomic characterization questionnaire (validated in the face and content); Minnesota Living With Heart Failure Questionnaire (MLHFQ); Health Questionnaire-EuroQol EQ-5D-3L. Proceeded to the statistical analysis is not Statistical Package for Social Sciences version 21.0, performing simple exploratory analysis Frequency, Student t test, ANOVA, Pearson and Spearman correlations. Hair design ethics committee approved, apparently No. 833.007. Patients were recruited (n=258) predominantly of males (53.39%), average age of 63 (± 11:42) years. The NYHA Functional Class II found the most was (43.80%) of hypertensive etiology (33.33%). Or MLHFQ demonstrated impact negative on HRQoL Gives IC under, with score of 23:53 (± 9:59) in the physical domain, 11.89 (± 4.83) points in emotional and 15:12 control (± 6:00) points in the General control so the total score of 50.54 ( ± 18:50) points. The EQ-5D-3L questionnaire showed que Patients with IC have some in problem Mobility (44.96%), problems we Personal care (28.29%), moderate problems Realization of customary in activities (51.16%), pain and moderate malaise (50% ) to severe (25.58%), and extremely anxious or depressed (35.66%). Significant associations (p = 00:00) between fri and were obtained you physical, emotional and overall the MLHFQ dominions; General working condition with domain (p = 0.01); With NYHA Functional Class I all areas of MLHFQ (p = 0:00); Surgical Procedure tools with emotional domain (p = 0:02) and overall (p = 0.01) and general alcoholism with domain (p = 0:04). The correlation between age and physical domain MLHFQ was weak (r = 0.153), the well or the total score (r = 0.134), but significant (p <0.05). A single negative correlations obtained income, weak and with significant physical or domains (r = -0,179; p <0.01), and total (r = -0,132; p <0.05) of the instrument. The Ejection Fraction of the Left Ventricle (LVEF) obtained with weak correlations and negative physical domain (r = -0 256; p <0.01), emotional (r = -0 152; p <0.05) and total (r = - 0.272; p <0.01) and moderate overall domain correlation (r = -0 272; p <0.01). The Visual Analogue Scale (VAS) and moderate negative correlation obtained with all areas of MLHFQ, p <0.01. The general correlation between HRQoL (EQ-5D-3L) and specific (MLHFQ) for IC were moderate to strong, and all with positive value of p <0.01. The negative impact IC scores you General and specific HRQoL.